2015
DOI: 10.17116/jnevro20151152116-20
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pain on quality of life before and after the surgical treatment of lumbar vertebral canal stenosis

Abstract: Before surgery, the patients had chronic pain syndrome of mixed etiology (nociceptive and neurotic type) and neurological disorders that significantly affected quality of life and work capacity. Neuropathic pain and depression, reduced quality of life and daily activities were more pronounced in patients with central canal stenosis compared to patients with lateral stenosis. The timely surgical treatment of lumbar vertebral canal stenosis promoted the decompression of nervous structures. A significant reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…21 In the case of cervical arthrodesis surgery, the results for improvement in quality of life were also evident in the literature, which reinforces the possibility that the low number of individuals analyzed who underwent the procedure on the cervical spine was responsible for the lack of statistical significance. 16,21 This study addresses a very important theme in the scientific productions on current surgery of vertebral spine, therefore it is essential to evaluate the real impact of the surgeries performed, and the costs of this type of treatment for the health services. This study therefore has local importance, showing that the investment in this type of procedure, for the patients evaluated, resulted in a significant gain in quality of life, improvement in pain and functional capacity, and importance for other services to show that the current conducts have proven efficient for the treatment of patients with injuries of the vertebral spine.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…21 In the case of cervical arthrodesis surgery, the results for improvement in quality of life were also evident in the literature, which reinforces the possibility that the low number of individuals analyzed who underwent the procedure on the cervical spine was responsible for the lack of statistical significance. 16,21 This study addresses a very important theme in the scientific productions on current surgery of vertebral spine, therefore it is essential to evaluate the real impact of the surgeries performed, and the costs of this type of treatment for the health services. This study therefore has local importance, showing that the investment in this type of procedure, for the patients evaluated, resulted in a significant gain in quality of life, improvement in pain and functional capacity, and importance for other services to show that the current conducts have proven efficient for the treatment of patients with injuries of the vertebral spine.…”
Section: Discussionmentioning
confidence: 71%
“…In Brazil, authors have found an improvement in ODI score after 2 years of lumbar arthrodesis, with a reduction from 61.04 before surgery to 34.15 after surgery, and results of the SF-36 with better results for the domains "Pain", "Emotional Aspects" and "Functional Capacity". 21 Data from European studies have shown an improvement in ODI, SF-36, Paindetect (PD) and Douleurneuropathique 4 (DN4) scores for surgery of the lumbar spine. 21 In the case of cervical arthrodesis surgery, the results for improvement in quality of life were also evident in the literature, which reinforces the possibility that the low number of individuals analyzed who underwent the procedure on the cervical spine was responsible for the lack of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation